Large Scale Monitoring of Web Application Software Distribution to Measure Threat Response Behavior - Marquardt, Fabian; Buhl, Lennart (Electronic Communications of the EASST, 2021)
Web application software may be affected by vulnerabilities and a fast deployment of security updates is required to protect users from attacks. With daily scans of over 50 million websites we are able to measure the threat response behavior. Preliminary results indicate significant differences between the different observed web application softwares.